2008
DOI: 10.1590/s1677-54492008000200014
|View full text |Cite
|
Sign up to set email alerts
|

Utilização da veia ilíaca externa recanalizada para implante de cateter de longa permanência para hemodiálise

Abstract: O uso de cateteres venosos cervicais para hemodiálise leva freqüentemente à oclusão dessas veias. Como alternativa, os acessos venosos femorais são válidos, porém o seu uso também está associado à oclusão dessas veias e a um maior índice de infecção. Vias alternativas são cada vez mais utilizadas na impossibilidade dos acessos previamente mencionados. Descrevemos neste relato de caso uma alternativa para o implante de cateter de longa permanência para hemodiálise usando a veia ilíaca externa recanalizada. Come… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…(Leiser, Tognim, & Bedendo, 2007) The predominance of infected patients admitted to the intensive care unit (ICU), the prevalence of very old male individuals was similar to previous studies (Grothe, Belasco, Bitencourt, Vianna, Sesso, & Barbosa, 2010;Moreira, Borges, Costa, Quinino, Serra, & Oliveira, 2008) The diabetic patients undergo constant changes and complications of disease, including risk of developing nephropathy (Oliveira, Alves, & Bezerra, 2009). Our study, however, found no relationship between kidney disease and this disease.…”
Section: Discussionsupporting
confidence: 89%
“…(Leiser, Tognim, & Bedendo, 2007) The predominance of infected patients admitted to the intensive care unit (ICU), the prevalence of very old male individuals was similar to previous studies (Grothe, Belasco, Bitencourt, Vianna, Sesso, & Barbosa, 2010;Moreira, Borges, Costa, Quinino, Serra, & Oliveira, 2008) The diabetic patients undergo constant changes and complications of disease, including risk of developing nephropathy (Oliveira, Alves, & Bezerra, 2009). Our study, however, found no relationship between kidney disease and this disease.…”
Section: Discussionsupporting
confidence: 89%